Improving the Resilience of Parents of Stunting Children through the Kalinting Program (Stunting Counseling Cadre) - Novita Wardani; Elisa Ulfiana; Lutfiana Puspita Sari; Eni Sulastri (Poltekkes Kemenkes Surakarta, 2026)
Background: Stunting remains a major problem in Indonesia. The Blora Regency Government targets a stunting prevalence of 20.81% by 2025. Stunting impacts parents' psychological well-being, such as feelings of inability to care for their children. Therefore, resilience and adaptation are needed to accept their child's condition. Parental resilience can be improved through social support and knowledge. Stunting counseling by cadres can provide social support and knowledge to mothers emotionally. The purpose is to analyze the effect of kalinting on resilience of parents of stunted children. Methods: This quantitative study used a single-group pretest-post test design. The population was all cadres in the stunting village. A sample of 30 cadres was selected using consecutive sampling. The study was conducted from June to September 2025 in Blora Regency. The independent variable was stunting counseling, while the dependent variables were cadre knowledge and maternal resilience. The knowledge and resilience instruments used a questionnaire. A pretest of cadre knowledge was conducted before counseling, and a posttest was conducted three days later. The pretest of maternal resilience in stunted children was conducted before the stunting counseling practice, followed by a posttest. Analysis used a paired t-test because the data were normal. Results: The results of the study showed a difference in the knowledge of cadres before and after education (p=0.0001) and a difference in the resilience of mothers before and after receiving counseling (p=0.0001). Conclusion: Stunting counseling by cadres can increase mothers' confidence in caring for their children. Cadres can provide stunting counseling at integrated health posts.